2004
DOI: 10.1038/modpathol.3800152
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Birt–Hogg–Dubé gene mRNA in normal and neoplastic human tissues

Abstract: Birt-Hogg-Dubé (BHD) syndrome is an inherited autosomal genodermatosis characterized by hamartomas of the hair follicle called fibrofolliculomas and an increased risk for developing spontaneous pneumothorax, lung cysts and renal neoplasia. BHD was localized to chromosome 17p11.2 by linkage analysis in BHD families, and germline insertion/deletion and nonsense mutations in a novel gene were identified which were predicted to prematurely truncate the BHD protein, folliculin. No homology to other human proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 16 publications
(12 reference statements)
6
79
1
2
Order By: Relevance
“…In all cases, the germline BHD mutant allele was retained, and the wild-type BHD allele was lost. Consistent with these results, BHD mRNA expression was hardly detectable in BHD-associated renal tumors by in situ hybridization (87). Studies are currently under way to identify the BHD gene function and to determine how alteration of this gene leads to kidney cancer (Fig.…”
Section: Bhd: Chromophobe Renal Cell Carcinomasupporting
confidence: 65%
“…In all cases, the germline BHD mutant allele was retained, and the wild-type BHD allele was lost. Consistent with these results, BHD mRNA expression was hardly detectable in BHD-associated renal tumors by in situ hybridization (87). Studies are currently under way to identify the BHD gene function and to determine how alteration of this gene leads to kidney cancer (Fig.…”
Section: Bhd: Chromophobe Renal Cell Carcinomasupporting
confidence: 65%
“…BHD mRNA is expressed in stromal cells and type I pneumocytes of the lung, suggesting that folliculin plays an important role in lung tissues (10). We have also reported that patients with BHDS are associated with the development of spontaneous pneumothorax (11).…”
Section: Birt-hogg-dubé Syndrome (Bhds; Omim [Online Mendelianmentioning
confidence: 88%
“…The BHD gene codes a protein named folliculin, which is expressed in skin tissue, nephrons, and type I pulmonary alveolar epithelial cells (5). Its functions are unknown, although it is reported to be involved in cell growth (6) and as a cancer-inhibitory gene on the basis of renal tumor analysis (7,8). The BHD gene is composed of 14 exons, and exon 11 includes a hot spot that easily develops gene mutation due to the continuous residence of a cytosine base at C8.…”
Section: Discussionmentioning
confidence: 99%